2020
DOI: 10.2147/jhc.s272535
|View full text |Cite
|
Sign up to set email alerts
|

<p>Amide Proton Transfer Imaging vs Diffusion Kurtosis Imaging for Predicting Histological Grade of Hepatocellular Carcinoma</p>

Abstract: Background: To investigate the value of amide proton transfer (APT) imaging in predicting the histological grade of hepatocellular carcinoma (HCC), compared with diffusion kurtosis imaging (DKI). Methods: A total of 88 patients with HCC were enrolled and divided into four groups (G1, G2, G3, and G4) based on histologic grades. Preoperative APT signal intensity (SI), mean diffusivity (MD), mean kurtosis (MK) of HCC were measured and compared. Those quantitative magnetic resonance imaging (qMRI) parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(52 reference statements)
2
8
0
Order By: Relevance
“…K and DK were positively and negatively correlated with the pathological grade, respectively. Moreover, Wu et al [44] found similar results, with higher-grade HCC showing lower DK and higher K values than lower-grade HCC. These findings are consistent both with results from Wang et al [43] and those by Cao et al [30].…”
Section: Studies On Dkimentioning
confidence: 70%
See 1 more Smart Citation
“…K and DK were positively and negatively correlated with the pathological grade, respectively. Moreover, Wu et al [44] found similar results, with higher-grade HCC showing lower DK and higher K values than lower-grade HCC. These findings are consistent both with results from Wang et al [43] and those by Cao et al [30].…”
Section: Studies On Dkimentioning
confidence: 70%
“…Nine of the included studies investigated the role of DKI model in HCC. Specifically, two of them investigated DKI for HCC diagnosis [45,54] and two for HCC grading [43,44]. Among the remaining five, two investigated the role of DKI for prediction of response to treatment [47,70], two assessed if DKI could be associated with prognostic factors [46,60], and the remaining one [30] investigated the power of DKI for both MVI prediction and histological grading assessment.…”
Section: Studies On Dkimentioning
confidence: 99%
“…Interestingly, some studies ( 22 , 25 , 34 ) have suggested that the D* or f values could predict HCC pathological grades, while other studies ( 18 , 35 , 39 ) did not confirm such conclusions. Our study suggested that there was no significant benefit of D* or f values in predicting HCC pathological grades.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, that meta-analysis did not summarize the diagnostic efficacy of IVIM-DWI parameters for MVI and did not analyze whether D*, f, MK, and MD could predict the pathological grade and MVI in individuals with HCC. In addition, it remains controversial whether D*, f, MK, and MD values could detect the HCC pathological grade or MVI before surgery ( 22 , 25 , 34 , 35 , 39 , 46 , 47 ).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional DWI data analysis approach is founded on the hypothesis that voxel water diffusion has a single component and follows a normal Gaussian distribution, and that water molecules diffuse without any constraint. However, water molecule diffusion within biologic tissue exhibits non-Gaussian behavior [123][124][125][126][127][128][129][130][131][132]. Jensen et al in 2005 reported a non-Gaussian diffusion model called Diffusion Kurtosis imaging (DKI) [123] used to analyze DWI data.…”
Section: Diffusion Weighted Imaging-mrimentioning
confidence: 99%